2018
DOI: 10.3233/jad-170834
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Genetic Architecture of Alzheimer’s Disease Risk in Rate of Memory Decline

Abstract: Many genetic studies for Alzheimer's disease (AD) have been focused on the identification of common genetic variants associated with AD risk and not on other aspects of the disease, such as age at onset or rate of dementia progression. There are multiple approaches to untangling the genetic architecture of these phenotypes. We hypothesized that the genetic architecture of rate of progression is different than the risk for developing AD dementia. To test this hypothesis, we used longitudinal clinical data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 49 publications
(50 reference statements)
3
50
0
Order By: Relevance
“…We sought to explore whether common AD risk alleles (identified via GWAS) contribute to variation in HC BOLD during scene encoding in young healthy individuals. While several studies have linked AD-PRS to memory [49][50][51] and structural brain changes across the lifespan [52][53][54], this work is amongst the first to quantify the relationships between AD-PRS and functional brain activity, specifically via task-based fMRI in AD vulnerable regions. More specifically, we used an embedded category localiser to target HC function in a large sample (N = 608), powered to detect relatively small effects.…”
Section: Discussionmentioning
confidence: 99%
“…We sought to explore whether common AD risk alleles (identified via GWAS) contribute to variation in HC BOLD during scene encoding in young healthy individuals. While several studies have linked AD-PRS to memory [49][50][51] and structural brain changes across the lifespan [52][53][54], this work is amongst the first to quantify the relationships between AD-PRS and functional brain activity, specifically via task-based fMRI in AD vulnerable regions. More specifically, we used an embedded category localiser to target HC function in a large sample (N = 608), powered to detect relatively small effects.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies were in healthy older adults, although two studies included participants with established AD/MCI [11,26], two studies had young adult participants [51,57], one study had adolescent participants [40] and one included longitudinal data from children aged 11 [59]. There were some cross-sectional studies that only reported associations with AD polygenic risk and cognition at one timepoint [40, 50-52, 54, 55, 57, 68], whereas longitudinal studies were able to report the correlations with change in cognition over time [11,26,31,33,36,44,45,56,60,[62][63][64]. As expected, most studies reported that the effects attenuated or were no longer significant when APOE was excluded from the PRS.…”
Section: Cognitive Measuresmentioning
confidence: 99%
“…Of these, cognition has been the most widely investigated. While the methodology and samples were diverse, the vast majority of studies reported significant associations [11,26,31,33,36,40,44,45,50,52,54,56,60,63,64,68,69]. Of the negative studies, one used a threshold-based PRS [59] and another used a PRS including 15 Bonferronisignificant risk SNPs [39] but both excluded APOE entirely.…”
Section: Associations Between Ad Prs Phenotypes and Biomarkersmentioning
confidence: 99%
“…Several studies have examined factors associated with cognitive decline in non-demented adults, [1][2][3][4][5][6][7][8][9] conversion from mild cognitive impairment (MCI) to AD, [10][11][12][13][14][15][16][17][18] and rate of cognitive decline (ROD) after AD diagnosis. [19][20][21][22][23][24][25][26] Several nongenetic determinants of decline, including lifestyle factors, biomarkers and biometric variables, and co-morbid diagnoses have also been reported. [26][27][28][29][30][31][32][33][34][35][36][37][38] Several genetic and epigenetic factors that may contribute to ROD in AD cases have also been identified.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26] Several nongenetic determinants of decline, including lifestyle factors, biomarkers and biometric variables, and co-morbid diagnoses have also been reported. [26][27][28][29][30][31][32][33][34][35][36][37][38] Several genetic and epigenetic factors that may contribute to ROD in AD cases have also been identified. Expression levels of leucine rich repeat and fibronectin type III domain containing 2 (LRFN2), 39 beta-nerve growth factor and its receptors, 40 myocyte-enhancer factor 2C, 41 and inositol polyphosphate-5-phosphatase 42 have been associated with ROD in the brains of people with AD.…”
Section: Introductionmentioning
confidence: 99%